A new empirical kinetic method for the determination of ion-exchange constants for the counterions of cationic micelles: The rate of piperidinolysis and hydrolysis of anionic phenyl salicylate as the kinetic probes - Khan, M.N.; Ismail, E.; Yusof, N.S.M. (Elsevier, 2010)
Pseudo-first-order rate constants (k(obs)) for the nucleophilic reaction of piperidine (Pip) with anionic phenyl salicylate (S(-)) in aqueous solution, obtained at constant content (=2%, v/v) of CH(3)CN, [Pip]T (=0.1 M), [S(-)](T) (=2 x 10(-4) M), [CTABr](T) (total concentration of cetyltrimethylammonium bromide), NaOH (<= 0.10 M) and varying concentration of inert salts, MX (=2-NaOC(6)H(4)CO(2)Na and 3-NaOC(6)H(4)CO(2)Na), follow the relationship: kobs,(ko oKx/simxivo + Kx/s, IMX]). derived from an empirical equation coupled with the pseudophase model of micelle. The empirical constants P and Kxis provide the respective parameters Fxis and Kx/s. The magnitude of Fxis gives the measure of the fraction of cationic micellized S- transferred to the aqueous phase by the limiting concentration of co-ions X- through the ion-exchange process X-/S-. In other words, the value of Fxis shows the cationic micellar penetration of ions X- relative to co-ions S. The values of Fxis and K(X/S) have been used to determine usual thermodynamic ion-exchange constant (K(X)(Y)). The values of K(X)(Y) (Y= Br) have been calculated for X = 2--OC(6)H(4)CO(2)(-) (2-0Bz(2-)) and 3-(-)OC(6)H(4)CO(2)(-) (3-OBz(2-)). The mean values of Kt are 44 +/- 7 and 4.9 0.7 for X- =2-0Bz2- and 3-0Bz2-, respectively. The value of K1 for 2-0Bz2- is nearly 9- and 16-fold larger than those for respective 3-0Bz2- and 4-006H4CO2- (4-OBz(2-)). These results are attributed to the presence and absence of viscoelasticity in CTABr aqueous solution with 2-0Bz2- and 3-0Bz2- as well as 4-0Bz2-, respectively. The mean values of Exis are 0.98 0.10. 0.24 0.07 and 0.14 0.02 for X- = 2-013z2-, 3-0Bz2- and 4-0Bz2-, respectively. The change in kinetic probe from piperidinolysis to hydrolysis of S- gives nearly same value, within the limits of experimental uncertainties, of IT for 2-0Bz2-. The mean value of Fxis x ((xis for 2-0Bz2- is decreased by 40-fold in the presence than in the absence of 0.05 M C16E20. 2010 Elsevier B.V. All rights reserved.